2015 IEEE Conference on Systems, Process and Control (ICSPC) 2015
DOI: 10.1109/spc.2015.7473558
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of ARX and ARMAX model based on PRBS and PRS perturbation

Abstract: This paper presents the comparison between ARX model and ARMAX model using the data from steam distillation essential oil extraction (SDEOE). The work is implementing system identification approach. The aim of this research is to identify the performance of ARX and ARMAX model toward the system. The input for every model is either Pseudo Random Binary Sequence (PRBS) or Pseudo Random Sequence (PRS) with temperature as output. Each dataset consists of 3000 sample, and being separated into estimation and validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…ACF of the input signal and CCF between input and output signal was used to estimate the transfer function model of the system [27]. In 2015, Ismail, et al compared ARX and ARMAX model performance using data from SDEOE, found that model fit for ARXs was between 95.77% and 95.06%, and the model fit for ARMAXs was between 95.68% and 95.05% [28].…”
Section: Arx Modelmentioning
confidence: 99%
“…ACF of the input signal and CCF between input and output signal was used to estimate the transfer function model of the system [27]. In 2015, Ismail, et al compared ARX and ARMAX model performance using data from SDEOE, found that model fit for ARXs was between 95.77% and 95.06%, and the model fit for ARMAXs was between 95.68% and 95.05% [28].…”
Section: Arx Modelmentioning
confidence: 99%